Freshening of the Adelie Land Bottom Water near 140°E - Aoki, S; Rintoul, SR; Ushio, S; Watanabe, S; Nathaniel Bindoff (2005)
Repeat summer hydrographic observations along 140°E are used to document significant changes in the properties of the Adélie Land Bottom Water (ALBW) between the mid-1990s and 2002–2003. Water on the 28.35 kg·m−3 neutral density surface cooled by 0.2°C and freshened by 0.03 psu between 1994 and 2002. By re-occupying the same stations in the same season, the effects of seasonal variability and spatial variability were minimised allowing the signal of water mass changes to be clearly identified. Comparison of the recent data to high quality historical observations shows that the ALBW also freshened between the late 1960s and the mid-1990s. Although there is insufficient data to construct a continuous time series, the simplest explanation of the observed changes is that there has been a long-term (>30 year) and continuing freshening of the source waters supplying bottom water to the Australian-Antarctic basin.